Cigarette Marketing and Smoking Culture in 1930s Canada - Robinson, Daniel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
This paper examines political-economic, cultural, and marketing changes during the 1930s that solidified the domestic tobacco industry and cigarette smoking as a socially normative practice. During this decade, farm production of cigarette tobacco grew exponentially in southern Ontario, as did cigarette manufacturing operations, mostly in Montréal. Cigarette marketing and advertising were prolific, as evidenced by the bevy of premium promotions, gift rebates, sports sponsorships, and athlete and celebrity testimonial advertising. Women, for the first time, were routinely targeted by cigarette advertising, and their entry into the ranks of “legitimate” smokers proved a watershed for tobacco manufacturers. Two specific developments further boosted the long-term viability of the cigarette industry. First, Canada’s dominant tobacco firm, Imperial Tobacco, spent heavily on public relations advertising to overcome public criticism of its cut-throat merchandising practices. Second, menthol and filtered cigarettes first appeared in the 1930s, ads for which reassured smokers worried about sore throats and persistent coughs. Long before the tobacco industry’s massive public relations response in the 1950s to the “cancer scare” (which included the heavy promotion of filtered brands as “safer” cigarettes), Imperial Tobacco, among others, was versed in issue-management public relations and forms of cigarette “health marketing.”